Post‐exercise hot water immersion induces heat acclimation and improves endurance exercise performance in the heat. Issue 7 (9th December 2015) - Zurawlew, M. J.; Walsh, N. P.; Fortes, M. B.; Potter, C.
Abstract : We examined whether daily hot water immersion (HWI) after exercise in temperate conditions induces heat acclimation and improves endurance performance in temperate and hot conditions. Seventeen non‐heat‐acclimatized males performed a 6‐day intervention involving a daily treadmill run for 40 min at 65% V̇O2max in temperate conditions (18 °C) followed immediately by either HWI ( N  = 10; 40 °C) or thermoneutral (CON, N  = 7; 34 °C) immersion for 40 min. Before and after the 6‐day intervention, participants performed a treadmill run for 40 min at 65% V̇O2max followed by a 5‐km treadmill time trial (TT) in temperate (18 °C, 40% humidity) and hot (33 °C, 40% humidity) conditions. HWI induced heat acclimation demonstrated by lower resting rectal temperature ( T re, mean, −0.27 °C, P  <   0.01), and final T re during submaximal exercise in 18 °C (−0.28 °C, P  <   0.01) and 33 °C (−0.36 °C, P  <   0.01). Skin temperature, T re at sweating onset and RPE were lower during submaximal exercise in 18 °C and 33 °C after 6 days in HWI ( P  <   0.05). Physiological strain and thermal sensation were also lower during submaximal exercise in 33 °C after 6 days in HWI ( P  <   0.05). HWI improved TT performance in 33 °C (4.9%, P  <   0.01) but not in 18 °C. Thermoregulatory measures and performance did not change in CON. Hot water immersion after exercise on 6 days presents a simple, practical, and effective heat acclimation strategy to improve endurance performance in the heat.